Exosome-Derived miRNAs in Liquid Biopsy for Lung Cancer - Israel Martínez-Espinosa; José A. Serrato; Carlos Cabello-Gutiérrez; Ángeles Carlos-Reyes; Blanca Ortiz-Quintero (Life, 2024)
Exosome-derived microRNAs (miRNAs) are potential biomarkers for lung cancer detection and monitoring through liquid biopsy. These small, non-coding RNA molecules are found within exosomes, which are extracellular vesicles released from cells. Their stability in biofluids, such as blood, positions them as candidates for minimally invasive diagnostics. Multiple studies have shown that lung cancer patients exhibit distinct miRNA profiles compared to healthy individuals. This finding suggests that exosome-derived miRNAs could serve as valuable biomarkers for diagnosis, prognosis, and evaluating therapeutic responses. This review summarizes recent research on exosome-derived miRNAs in liquid biopsies, including blood, pleural effusion, and pleural lavage, as biomarkers for lung cancer, focusing on publications from the last five years.